Rotational thromboelastometry for diagnosis of fibrinolysis induced by urokinase in an in-vitro model. Issue 1 (January 2022) - Bevilacqua, Sergio; Paniccia, Rita; Galeotti, Ilaria; Viappiani, Anna; Dimizio, Fabio; Bartolozzi, Carlo; Marcucci, Rossella; Stefàno, Pierluigi
Abstract : N/A: Fibrinolysis can be abnormally activated in several critical care settings but it's often misdiagnosed by standard laboratory tests. Although rotational thromboelastometry can assess the whole coagulative process, its ability to detect fibrinolysis has been questioned. Aim of this study was to investigate the ability of thromboelastometry in detecting induced fibrinolysis in an in-vitro model. Whole blood samples were taken from 18 healthy volunteers. Each sample was split and added with increasing urokinase concentrations till to reach 0, 50, 75 and 100 IU/ml. Thromboelastometry tests, extem and aptem, were performed on the obtained samples. If significant lysis at 50 IU/ml was recorded, also 10, 25 and 35 IU/ml drug concentrations were tested. No lytic effects were detected in 10 IU/ml samples. Lysis variables were the most sensitive in detecting fibrinolysis even at 25 IU/ml ( P  < 0.05). Clot firmness parameters were also affected by urokinase, but only at the two highest drug concentrations ( P  < 0.05). Extem/aptem ratio enhanced the sensitivity of these parameters only if lysis was more marked. Analysing groups of different lysis severity, the time to achieve maximum clot firmness could anticipate an ongoing fulminant or intermediate lysis with 100% sensitivity and 100% specificity ( P  < 0.05) when lower than 1341.5 s. Rotational thromboelastometry could detect fibrinolysis when it was induced in vitro by 25 IU/ml urokinase or more. Apart from the parameters specific for lysis, time to achieve maximum clot firmness appeared as the earliest indicator of fibrinolysis with high sensitivity and specificity especially if a more intense lysis was going on.